2015
DOI: 10.1590/1414-431x20143965
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the effects of insomnia and night work on cardiovascular diseases: a study in nursing professionals

Abstract: Cardiovascular diseases (CVDs) are known to be associated with poor sleep quality in general populations, but they have not been consistently associated with specific work schedules. Studies of CVD generally do not simultaneously consider sleep and work schedules, but that approach could help to disentangle their effects. We investigated the association between insomnia and a self-reported physician diagnosis of CVD in day and night workers, considering all sleep episodes during nocturnal and diurnal sleep. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
(38 reference statements)
1
10
0
1
Order By: Relevance
“…The mediating effects of insomnia in the association between night shift and disturbed physiological and psychological health status had been reported in previous studies 11 17 18. That suggested that the disturbance of the internal circadian rhythm and/or insufficient recovery due to sleep disorders might play an important role in mediating the effects of shift work on workers' mental health risk.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The mediating effects of insomnia in the association between night shift and disturbed physiological and psychological health status had been reported in previous studies 11 17 18. That suggested that the disturbance of the internal circadian rhythm and/or insufficient recovery due to sleep disorders might play an important role in mediating the effects of shift work on workers' mental health risk.…”
Section: Discussionmentioning
confidence: 62%
“…Gender-stratified analyses were carried out because we anticipated that shift work may affect men and women in a different manner. Since previous studies suggested that sleep disturbances, rather than shift work per se, increase the health risks in shift workers,11 17 18 we also examined the associations of shift work with burnout and minor mental disorders after controlling for insomnia, to evaluate the potential mediating effects of insomnia.…”
Section: Introductionmentioning
confidence: 99%
“…13 The Swedish study by Asplund shows that nightmares were associated with an increased risk in irregular heartbeat and spasmodic chest pain in elderly people. 21 Studies have also reported that insomnia, [22][23][24] difficulty falling asleep, 10,25 and the use of sleeping pills 26 were related to an increased risk of cardiovascular disease. Although different methods were used for evaluating sleep quality, our results are in line with the results in the findings in previous literature.…”
Section: Discussionmentioning
confidence: 99%
“…Com efeito, o cuidado de enfermagem envolve mais do que um simples fazer, envolve compromisso, responsabilidade, conhecimento, vínculo e acolhimento. Ressalta-se que o estabelecimento de uma relação adequada entre profissional e usuário, o diálogo/comunicação, o conforto dos acompanhantes, uma assistência com enfoque na segurança do paciente e a integralidade na saúde mantida em ambientes intra e extra-hospitalar contribuem para a humanização da assistência, pois o cuidar pressupõe além do saber técnico, um olhar amplo que possibilita conhecer o ser humano em sua totalidade, relacionar-se 28,29 . É oportuno destacar assim, a necessidade de um atendimento mais rigoroso e individualizado aos pacientes com hipertensão, através de uma equipe multidisciplinar que busque avalia-los de forma holística, abrangendo todo o contexto político, social em que estão inseridos.…”
Section: Vínculounclassified